Road Traffic Accidents and the Traumatic Brain Injuries: A Cross- Sectional Study (Medico Legal Update, 2021)
Background: Street traffic accidents were a main community healthiness problematic particularly in lowand middle-income countries, head injuries were found to be the most common injuries. Objectives: toidentify the relationship of road traffic injuries with different associated factors.Methodology: This was a cross sectional study conducted on 500 Road Traffic Accidents victims admitted tothe emergency unit at Al-Sader Teaching General Hospital in Al Najaf Holy province- Iraq. Data collectionwas done using a pretested questionnaire. A medical team including neurosurgeon, medical, and orthopedicsto identify the types (pattern) of cranio-cerebral injuries evaluated outcomes of the injury cases.Results: Most of the victims are males in their productive age, motorcycle is the most common cause ofaccidents, head injuries constituted the highest proportion (39.6%), the mortality rate was (13.6%), andunhealthy behaviors during driving were dominated.Conclusion: Cerebral contusions and skull fractures were the most common lesions among head injuriesand trauma brain injuries victims.